Study on the relation between some enzyme and protein polymorphism and the zebra mussel organism response to pesticide exposure - Stoyanov, Ivan; Vasileva, Penka (Journal of BioScience and Biotechnology, 2024)
In the present study, a biochemical-genetic analysis was performed to determine the relationship between isoenzyme polymorphism and the zebra mussel Dressena polymorpha organism response to the harmful effects of the pesticides Cypermethrin and Chlorpyrifos. The probable genetic control of four enzyme and protein groups - malate dehydrogenase, malate enzyme, superoxide dismutase, and soluble proteins - was determined as well. Different intensities of expression of allelic products have been reported in individuals exposed to short- and long-term exposure to the pesticides Cypermethrin and Chlorpyrifos. The observed variability in the expression of superoxide dismutases, malate dehydrogenases, and soluble proteins in control and experimental samples gives us reason to accept these enzyme and protein systems as markers for reporting the negative impact of the tested pesticides on the zebra mussel.